(untitled) (Annals of Medical Research, 2021)
Aim: Osteoarthritis (OA) is a common joint disease which is caused by the effects of mechanical, genetic and biochemical factors. In studies conducted in recent years, it has been shown that osteoblasts play roles in OA pathogenesis. In this study, we investigated the relation between the level of preptin, which is known to have an effect on osteoblast proliferation and differentiation, bone metabolism, and the OA disease.Materials and Methods: A total of 40 healthy control patients and 40 women who were diagnosed with knee OA were included in the present study. The plasma preptin levels of the individuals who were included in the study were measured with Enzyme-linked Immuno-Sorbent Assay (ELISA) Method. Blood glucose, triglyceride, High-Density Lipoprotein Cholesterol (HDL-c), Low-Density Lipoprotein Cholesterol (LDL-c), total cholesterol levels and Body Mass Indices (BMI) leukocyte, lymphocyte, neutrophil, Erythrocyte Sedimentation Rate (ESR), C-Reactive Protein (CRP) of all participants were measured.Results: The preptin levels of the knee OA patients in plasma were significantly lower (206 ± 103 ng/L) compared to the healthy control Group (501 ± 525 ng/L) (p0.001). In addition, the (CRP) levels (p0.02) and the Body Mass Indices (BMI) (p0.001) were also higher in the OA Group compared to the Control Group. Conclusion: In the present study, it was determined that there is a significant relation between knee OA disease and plasma preptin levels. Preptin may have roles in the pathogenesis of the OA disease. Further studies are needed to elucidate the mechanisms through which molecular mechanisms preptin is related to knee OA. Keywords: Osteoarthritis; knee; preptin; ELISA; plasma.